Negative Histology after Endoscopic Resection: A Pathologist’s Aspect - So Jeong Lee; Do Youn Park (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Endoscopic biopsy is the most popular diagnostic procedure for gastric epithelial neoplasm. However, discrepancy between biopsy and endoscopic resection diagnosis occasionally occurs and leads to an unnecessary procedure. A negative pathologic diagnosis following endoscopic resection is particularly problematic. In this context, we reviewed factors that may be associated with a diagnostic discrepancy between endoscopic biopsy and endoscopic resection, with focus on crypt dysplasia.